MOTIF BERGABUNG DALAM ALIRAN SAPTA DARMA PENGIKUT AJARAN DI SANGGAR AGUNG CANDI SAPTA RENGGA YOGYAKARTA - Nur Arifin (Jurnal Sosiologi Agama, 2017)
The flow of Sapta Darma is part of the religion and belief that exists in Indonesia, especially in Yogyakarta as the center of its development. This study explains the motives of people to join the flow of Sapta Darma in Yogyakarta and how the influence that can be for followers is also the response of society in general. This research uses qualitative case study approach through observation, interview, and documentation.The results of this study show that; First, the motive follows the flow of Sapta Darma, on the grounds that there is a worthy value with the rational foundation of values, the expectation to be accomplished with an instrumental foundation, preserving its generation with a traditional foundation, and a deep feeling. Second, the peace of the soul, living in peace and giving the teachings of tolerance, having the spiritual power of being an example to society. Third, Sapta Darma’s beliefs are accepted by the reason of this group relating to human rights, while others refuse to come from the extreme.Keywords: religion, class, motive, social action approach.